2020
DOI: 10.1186/s12879-020-05648-6
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster risk and burden of disease in immunocompromised populations: a population-based study using health system integrated databases, 2009–2014

Abstract: Background Estimate the incidence of herpes zoster (HZ), its complications and healthcare utilization rates in adults (≥ 18-years-old) with a wide range of immunocompromised (IC) conditions compared to IC-free cohort. Method A population-based retrospective study using the Valencia healthcare Integrated Databases (VID) (2009–2014). HZ and IC were defined using ICD-9 codes in primary care (PC) and hospitalization registers. Incidence rates (IR), ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 42 publications
2
57
0
Order By: Relevance
“…Furthermore, there are no other studies reporting the risk for a second recurrence or recurrence for patients with UCs. However, a recent study from Spain reported significantly higher recurrence rates in immunocompromised patients [ 58 ]. This result is in line with the results presented here which show that patients with UCs have a higher risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are no other studies reporting the risk for a second recurrence or recurrence for patients with UCs. However, a recent study from Spain reported significantly higher recurrence rates in immunocompromised patients [ 58 ]. This result is in line with the results presented here which show that patients with UCs have a higher risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Spain is similar; large retrospective studies have reported incidence rates of 5.0/1000 PY in adults aged 18 years or older [ 16 ], and 7.2/1000 PY in those aged 50 years or older [ 17 ]. Similar to other countries, higher incidence is reported in women and in the immunocompromised, and in patients with specific comorbidities such as COPD [ 16 18 ]. PHN is estimated to develop in between 12% and 16% of patients [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 91%
“…The proportion of those patients with HZ who develop PHN in recent studies from Italy, Germany, and the UK ranges between 10% and 12% [13][14][15]. Data from Spain is similar; large retrospective studies have reported incidence rates of 5.0/ 1000 PY in adults aged 18 years or older [16], and 7.2/1000 PY in those aged 50 years or older [17]. Similar to other countries, higher incidence is reported in women and in the immunocompromised, and in patients with specific comorbidities such as COPD [16][17][18].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Virus reactivation occurs when the immune system is suppressed. Increased HZ incidence, attributed to a decline in immunity, is observed in elderly people and in patients using immunosuppressive medication (2)(3)(4)(5)(6)(7)(8)(9)(10). The latter certainly applies to solid organ transplant recipients.…”
Section: Introductionmentioning
confidence: 99%